Monetary theory and public policy - Kurihara, Kenneth K. ([S.l.] : Routledge, 1962)
Providing an extensive examination of monetary theory and its implications for public policy, Monetary Theory and Public Policy is as relevant for an understanding of current economic problems as when it was first published. Looking at the concepts of modern economic theory, particularly as these concepts apply to problems of money and banking, both Keynesian and Post-Keynesian developments are discussed.